Effect of Zinc Applications on Quality Parameters of Wheat in Semi Arid Region - Kinaci, Gulcan; Kinaci, Engin (Asian Journal of Chemistry, 2010)
Effect of zinc application methods on 1000 kernel weight, protein content, sedimentation, gluten, gluten index and starch damaged of wheat was studied. Zinc applied to soil, to seed, to leaf, to soil+ leaf and to seed+leaf. Experimental design was factorial in randomized complete block with three replications. Investigated traits affected positively by all zinc treatments. Soil + leaf and soil application of zinc were most effective. Variation observed among wheat genotypes in response to zinc.